FAKTOR PENDORONG EKSPOR PRODUK TEKSTIL INDONESIA KE AMERIKA - Yeniwati Yeniwati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
This study aims to analyze effect of export prices and United States income on export textile Indonesia to The United State. Types of data used are secondary data from 1982 until 2011. Analysis of the data used the OLS Method. The results are export prices and United States income significant effect on exports of textiles Indonesia to the United States. It can be seen from positive coefficient value and significant.